Association between vascular access failure and microparticles in hemodialysis patients - Jung-Hwa Ryu; Su-Young Lim; Dong-Ryeol Ryu; Duk-Hee Kang; Kyu Bok Choi; Seung-Jung Kim (The Korean Society of Nephrology, 2012)
Background: Vascular access failure, a major cause of morbidity in hemodialysis (HD) patients, occurs mainly at stenotic endothelium following an acute thrombotic event. Microparticles (MPs) are fragments derived from injured cell membrane and are closely associated with coagulation and vascular inflammatory responses. Methods: We investigated the relationship between levels of circulating MPs and vascular access patency in HD patients. A total of 82 HD patients and 28 healthy patients were enrolled. We used flow cytometry to measure endothelial MPs (EMPs) identified by CD31+CD42− or CD51+ and platelet-derived MPs (PMPs) identified by CD31+CD42+ in plasma samples of participants. Vascular access patency was defined as an interval from the time of access formation to the time of first access stenosis in each patient. MP counts were compared according to access patent duration. Results: The levels of EMP (both CD31+CD42− and CD51+) and CD31+CD42+PMP were significantly higher in patients than in healthy participants. Levels of CD31+CD42−EMP and CD31+CD42+PMP showed a positive correlation. In non-diabetic HD patients, CD31+CD42−EMPs and CD31+CD42+PMPs were more elevated in the shorter access survival group (access survival <1 year) than in the longer survival group (access survival ≥ 4 years). Conclusion: Elevated circulating EMP or PMP counts are influenced by end-stage renal disease and increased levels of EMP and PMP may be associated with vascular access failure in HD patients.